On leadership : an interdisciplinary approach - Fowler, Denver J.; Raehll, Meghan B. (Emerald Publishing Limited : Information Age Publishing, Inc., 2022)
"In On Leadership: An Interdisciplinary Approach editors Fowler and Raehll provide one of the most comprehensive books on interdisciplinary leadership approaches to date. Contributing authors from across the nation and around the globe include individuals from an array of sectors, including Education (PK-12 and Higher Education), Business, Public and Nonprofit Organizations, Government, Military, Law Enforcement, and the Healthcare Industry. With a focus on highlighting the best practices as it applies to effective leadership in any given organization, the book offers a much needed analysis of what it means to lead successfully in the 21st Century and beyond"--